2012
DOI: 10.1155/2012/417935
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Molecular Aspects of Indian Tomato Leaf Curl Virus Coat Protein

Abstract: Tomato leaf curl disease (ToLCD) is manifested by yellowing of leaf lamina with upward leaf curl, leaf distortion, shrinking of the leaf surface, and stunted plant growth caused by tomato leaf curl virus (ToLCV). In the present study, using computational methods we explored the evolutionary and molecular prospects of viral coat protein derived from an isolate of Vadodara district, Gujarat (ToLCGV-[Vad]), India. We found that the amino acids in coat protein required for systemic infection, viral particle format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
4
10
0
Order By: Relevance
“…But in the case of OW viruses the sequence diversification of cp and rep gene has been found to be similar. Previous studies have reported that cp is conserved among geminiviruses, different begomoviruses and in the Indian strain of ToLCV [11,19,25,28,29]. In the present study comparative diversity analysis of the genes in OW and NW viruses has been investigated.…”
Section: The Nw Cp Genes Under Purifying Selectionmentioning
confidence: 86%
See 1 more Smart Citation
“…But in the case of OW viruses the sequence diversification of cp and rep gene has been found to be similar. Previous studies have reported that cp is conserved among geminiviruses, different begomoviruses and in the Indian strain of ToLCV [11,19,25,28,29]. In the present study comparative diversity analysis of the genes in OW and NW viruses has been investigated.…”
Section: The Nw Cp Genes Under Purifying Selectionmentioning
confidence: 86%
“…The results suggest that probably the NLS sequences at N-terminal are gradually disappearing from NW coat proteins and the intracellular [3,13,25,27,57,58]. The NLS motif in coat protein is demonstrated to help in nuclear targeting of the OW viruses like MYMV [13], TYLCV [25], and ACMV [58]. Ha et al [15] have reported that the jute infection CoGMV and CoYVV lacks the second and third basic domain in the N-terminal region of coat protein like some other NW viruses.…”
Section: Nls Sequence In Nw Cp Genementioning
confidence: 96%
“…As these procedures yielded one close homologs. So, we choose to go for homology modeling of coat protein using online swiss model web server (https://swissmodel.expasy.org/) (Patel and Kalaria, 2018;kumar et al, 2012).…”
Section: Structure Modeling Of Coat Proteinmentioning
confidence: 99%
“…Most of the similar ligands score a docking energy within this energy error window (reference molecule docking energy ± 2.63 kcal/mol) making it difficult to prioritize compounds amongst false positive hits. With ongoing efforts on development of computational strategies on medicinal plants based drug discovery, structural bioinformatics and related methods (Kumar et al ., ; Kumar et al ., , ), we propose here a knowledge‐based approach wherein classical docking, quantitative‐structure activity relationship (QSAR) and machine learning models can be efficiently integrated to prioritize compounds from each method and identify a set of common molecule. We used Autodock Vina program (Trott and Olson, ) for docking, VLifeMDS molecular field point‐based 3D QSAR (MFP‐QSAR) for QSAR modelling, and shape and electrostatic similarity descriptors (along with MFP descriptors) to develop multilayer perceptron (MLP) models.…”
Section: Introductionmentioning
confidence: 99%